CAUSE-RELATED MARKETING: MODERATION EFFECT OF CUSTOMER VALUES ON THE INFLUENCE OF CAUSE-BRAND FIT, FIRM MOTIVES AND ATTRIBUTE ALTRUISTIC TO CUSTOMER INFERENCE AND PARTICIPATION INTENTION - Halim Rizal Edy; Adiwijaya K.; Fauzan R. (Universitas Hayam Wuruk Perbanas, 2013)
This study develops a conceptual model of Cause-related Marketing (CrM) investigating the effect of cause-brand fit, firm motives and altruistic attribution to customer inference and participation intention moderated by customer values. The approach used is quantitative where data are collected through a surveyusing non-probability sampling techniques. The sample was formed by consumers of Bottled Drinking Water Aqua brand and data was analyzed through structural equation modeling and multi-group analysis to test the hypothesis of moderation on the model. The findings in this study show consumers may use brand attitude before they participate in behavior intention that formed through CSR perception, brand credibility and altruistic attribution using firm social motives and cause-brand fit inCrM campaign. The results confirm lower altruists consumers use mainly altruistic attribution to form their judgment on brand credibility. They also employ cause-brand fit and firm motives to shape their decision on CSR perception in CrM messages.